Recycling Billet Scales as Fine Aggregate in Concrete Production - Akindahunsi A. A.; Ojo O (Civil Engineering Dimension, 2008)
Billet scales are by-products from steel rolling mills in Nigeria that presently constitute environmental pollution. This paper reports studies carried out using these solid wastes as a partial replacement for sand in the production of concrete. Various percentages of billet scales were used in a concrete mixture of 1: 2: 4 by weight to cast concrete specimens. The compressive and tensile strengths developed were tested after 7, 14, 21, and 28 days of curing. The result of the compressive and splitting tensile strengths tests indicated that concrete strength increased with curing age. The compressive strength of 0%, and 15% replacement of sand with billet scales as obtained at 28 days are 26.0N/mm2, 26.2N/mm2. 15% optimal replacement of sand with billet scales had similar results as the control mixture of 0%, which could be used in reinforced concrete structures. Other replacements could be useful as mass concrete for non-structural construction applications.